PRAGMATIC TRANSFER IN COMPLIMENT RESPONSE STRATEGIES OF THE ENGLISH DEPARTMENT STUDENTS OF STATE UNIVERSITY OF SEMARANG (English Education Journal, 2015)
This thesis is a pragmatic study about the pragmatic transfer in compliment responses strategies applied by the students of Semarang State University based on the compliment types, language difference, and English proficiency level. The participants of this study were 40 students, 20 students of undergraduate and postgraduate. The data were collected by implementing the naturalized role play conductors which is proposed by Tran (2010). Then, The data collected were analyzed based on the Tran’s (2007) compliment responses continuum hypothesis classification. After that, the data collections were analyzed based on the Kasper (1992) classification of pragmatic transfer; pragmalinguistic and socipragmatic transfer. The result of this study showed that the students of Semarang State University compliment responses strategies are eligible to Tran’s compliment responses framework classifications. The most frequently strategies used either in English and Bahasa is Appreciation token. This strategy was the most frequently used in both English and Indonesian version. In Bahasa Indonesia version it shared the top position with the compliment downgrade strategy. The language difference had influenced their response strategy. They are influenced by their L1 pragmatic awareness in responding the compliment of their L2 communication. It means that pragmalinguistic and socio-pragmatic transfer occurred in their responses strategies.